2016
DOI: 10.1088/0268-1242/32/1/013002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast non-equilibrium carrier dynamics in semiconductor laser mode-locking

Abstract: Experimental and theoretical results on the mode-locking dynamics in vertical-external-cavity surface-emitting lasers with semiconductor and graphene saturable absorber mirrors are reviewed with an emphasis on the role of nonequilibrium carrier effects. The systems are studied theoretically using a fully microscopic many-body model for the carrier distributions and polarizations, coupled to Maxwell's equations for the field propagation. Pump-probe measurements are performed with (sub-) 100 fs resolution. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…FCN), time-resolved Z-scan measurements would be required40 . In addition, the variation of the probe-pulse duration while maintaining equivalent peak powers could provide insight into the nature of the carrier dynamics including the effect of non-equilibrium many-body effects, which become important at sub-ps time-scales41 . This will be the subject of our future work.If BEKE is the dominating contribution to the nonlinear lensing, self-mode-locking of VECSELs has to be modeled by substituting the slow, highly nonlinear saturable absorber term with a fast saturable C. Kriso et al (2018) 10 absorber term in the common mode-locking model42 (c.f.Figure 4bon pulse shaping).…”
mentioning
confidence: 99%
“…FCN), time-resolved Z-scan measurements would be required40 . In addition, the variation of the probe-pulse duration while maintaining equivalent peak powers could provide insight into the nature of the carrier dynamics including the effect of non-equilibrium many-body effects, which become important at sub-ps time-scales41 . This will be the subject of our future work.If BEKE is the dominating contribution to the nonlinear lensing, self-mode-locking of VECSELs has to be modeled by substituting the slow, highly nonlinear saturable absorber term with a fast saturable C. Kriso et al (2018) 10 absorber term in the common mode-locking model42 (c.f.Figure 4bon pulse shaping).…”
mentioning
confidence: 99%
“…The characteristic timescale for gain recovery is on the order of tens of picoseconds or longer, which is orders of magnitudes slower than the carrier scattering [46]. Numerical tests show that the details of the results are not critically sensitive on the exact choice of τ scatt .…”
Section: Microscopic Theorymentioning
confidence: 93%
“…Through systematic numerical simulations we have found that the final mode locked pulse can be one of four different types 18,22 : a stable and an unstable single pulse, an unstable pulse molecule or multiple pulses. For a single stable pulse, there is only one pulse propagating in the cavity and the output has constant amplitude and FWHM.…”
Section: Pulse Familymentioning
confidence: 99%